209| Jurnal Administrasi Bisnis Vol 4 No 3 Juni 2024 PENGARUH PROMOSI DAN HARGA TERHADAP KEPUASAN PELANGGAN DI BUNDA BIC CLINIC VIDA BEKASI - Melviana, Dewi; Susmonowati, Trinik (JAMBIS : Jurnal Administrasi Bisnis, 2024)
Patient satisfaction can be achieved if the needs, desires, and expectations can be fulfilled through the services they receive. One of the factors is the cost incurred. The price set must be appropriate and follow the patient's income. Another aspect that can increase the number of consumers is promotion. Promotion plays an essential role in communicating the product's value to potential customers. This research aims to determine the effect of promotion and price on customer satisfaction at Bunda BIC Clinic Vida Bekasi. The research method used is the descriptive quantitative method. The data collection technique used is primary data distributed through questionnaires. The number of samples involved was 110 respondents. This research was conducted at Bunda BIC clinic Vida Bekasi. The data analysis used was multiple linear regression analysis processed on the SPSS software version 24. The results showed that promotion and price partially have a significant positive effect on customer satisfaction. Promotion and price simultaneously significantly affect customer satisfaction at Bunda BIC Clinic Vida Bekasi by 26.2%. While the remaining 73.8% is influenced by other variables or factors outside this research. From the results of this research, it is expected that the clinic management can maximize the use of social media for promotion and reach more customers. In addition, it is necessary to collaborate with influencers with thousands of active followers on social media.